Comparative Study Between Modified Computed Tomography (CT) Severity Index and Ranson Score in Predicting Severity of Acute Biliary Pancreatitis - Nazir, Fahad; Ilyas, Sohail; Sheikh, Imran; Shakeel, Hamza; Muhammad Faaiz Ul Maraam; Muhammad Shuja Hasan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the accuracy of the Modified CT Severity Index(mCTSI)and Ranson score for predicting severity of acute biliary pancreatitis.Study Design: Comparative Observational Study.Place and Duration of Study:  Department of Surgery, Combined Military Hospital, Rawalpindi Pakistan from Sep 2024 to Aug 2025.Methodology: Patients aged 18 to 60 years of age, with acute biliary pancreatitis were included. Ranson score and Modified CT severity Index were calculated. The Revised Atlanta Classification was used as reference standard for true severity assessment, categorizing patients into mild, moderately severe and severe acute pancreatitis. Measures of diagnostic accuracy of the Ranson Score and Modified CTSI in predicting severe pancreatitis as defined by the Revised Atlanta Classification were assessed. Receiver operating characteristic (ROC) curves were generated and area under the curve (AUC) was calculated for both scoring systems.Results: A total of 140 patients with acute biliary pancreatitis were included, with a median age of 41.00 (IQR 14.00) years. For predicting severe acute pancreatitis, the mCTSI demonstrated better performance, with a sensitivity of 84.4%, specificity of 92%, and accuracy of 87.1%, compared with Ranson score, which showed a sensitivity of 84.4%, specificity of 54%, and accuracy of 73.6%. ROC curve analysis yielded an AUC of 0.76 (95% CI: 0.677–0.842; p